THE INFLUENCE OF INTERNET EASE AND INTERNET USEFULNESS TOWARD USER ATTITUDE AND USER BEHAVIOR (Study on Undergraduate Students of Business Administration Department at The Faculty of Administrative Science of Brawijaya University) - Dimas Permana (Jurnal Administrasi Bisnis, 2013)
The results of this study concluded that the variable of Internet Ease (X1) has significance influence toward variable of Internet Usefulness (X2), the variable of Internet Ease (X1) has significance influence toward variable of User Attitude (Z), then for the variable of Internet Usefulness (X2) has significance influence toward variable of User Attitude (Z), but the variable of Internet Usefulness (X2) has no significance influence toward variable of User Behavior (Y), while the variable of User Attitude (Z) has significance influence toward variable of User Behavior (Y). Keywords: Internet Ease, Internet Usefulness, User Attitude, User Behavior